Addition of the Aldose Reductase Inhibitor Benzofuroxane Derivative BF-5m to Prolonged and Moderate Exercise Training Enhanced Protection of the Rat Heart From Type-1 Diabetes - Ferraro, Bartolo; Donniacuo, Maria; Sodano, Loredana; Ferraraccio, Franca; Maisto, Rosa; Gulotta, Eliana; Pieretti, Gorizio; D’Amico, Michele; Trotta, Maria Consiglia; Rinaldi, Barbara (Frontiers in Pharmacology, 2019)
Moderate exercise training may not be sufficient to exert beneficial effects on the cardiovascular system because of the long-term multifactorial etiology of diabetic complications. The addition of a proper pharmacological tool to the physical exercise should improve the outcomes of the diabetic damage. Here it is shown that 8 weeks exercise training of type 1 diabetic Sprague-Dawley rats resulted in a significantly increased heart rate, a 14% increase in the left ventricular ejection fraction increased plasma insulin levels and a 13% decrease in plasma glucose with respect to sedentary animals. The training also resulted in a 22% reduction in cardiac QT interval from a diabetic sedentary value of 185±19 milliseconds. Treatment of trained rats with the new antioxidant and NO-releasing aldose reductase 2 inhibitor 5(6)-(benzo[d]thiazol-2-ylmethoxy) benzofuroxane BF-5m, 20 mg/kg/day, added a further and significant (P < 0.01 vs sedentary) increase of the left ventricular ejection fraction up to 38% at 8 week time point. The long QT interval recorded in trained rats was reduced to further 12% by addition to the training of pharmacological treatment with 20 mg/kg/day BF-5m. At this time, the association of the two treatments improved the expression into the cardiac tissue of sarcoplasmic reticulum Ca2+ ATPase 2 (SERCA2) and manganese superoxide dismutase (MnSOD), and reduced the fibrosis.